Deleting an xylosidase-encoding gene VdxyL3 increases growth and pathogenicity of Verticillium dahlia - Li, Yongtai; Song, Shenglong; Chen, Bin; Zhang, Yong; Sun, Tiange; Ma, Xiaohu; Li, Yanjun; Sun, Jie; Zhang, Xinyu (Frontiers in Microbiology, 2024)
Verticillium dahliae causes a devastating Verticillium wilt disease on hundreds of plant species worldwide, including cotton. Understanding the interaction mechanism between V. dahliae and its hosts is the prerequisite for developing effective strategies for disease prevention. Here, based on the previous observation of an xylosidase-encoding gene (VdxyL3) in V. dahliae being obviously up-regulated after sensing root exudates from a cotton variety susceptible to this pathogen, we investigated the function of VdxyL3 in the growth and pathogenesis of V. dahliae by generating its deletion-mutant strains (ΔVdxyL3). Deleting VdxyL3 led to increased colony expansion rate, conidial production, mycelial growth, carbon and nitrogen utilization capacities, and enhanced stress tolerance and pathogenicity of V. dahliae. VdxyL3 is a secretory protein; however, VdxyL3 failed to induce cell death in N. benthamiana based on transient expression experiment. Transcriptomic analysis identified 1300 genes differentially expressed (DEGs) between wild-type (Vd952) and ΔVdxyL3 during infection, including 348 DEGs encoding secretory proteins, among which contained 122 classical secreted proteins and 226 non-classical secreted proteins. It was notable that of the 122 classical secretory proteins, 50 were carbohydrate-active enzymes (CAZymes) and 58 were small cysteine rich proteins (SCRPs), which were required for the pathogenicity of V. dahliae. The RNA-seq data thus potentially connected the genes encoding these proteins to the pathogenesis of V. dahliae. This study provides an experimental basis for further studies on the interaction between V. dahliae and cotton and the pathogenic mechanism of the fungus.